Developing Graded English Tasks (GET) for Differentiated English Instruction at Junior High School - Fajariyah, Laily Amin (Jurnal Didaktika Pendidikan Dasar, 2024)
Learning that accommodates the needs of all students is necessary in the classroom. However, in schools that provide inclusive education, the needs of special needs students are often overlooked. In this study, differentiated instruction using graded tasks was chosen to overcome the problem. This study aims to develop graded English tasks (GET) to accommodate the different readiness to learn and needs of special needs students in the classroom. This research is a Research and Development (R&D) study conducted using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data in this study were collected through questionnaires, performance assessments, reflections, observations, and interviews. Furthermore, quantitative data in this study were analyzed with descriptive statistics. Qualitative data were analyzed using Bogdan & Biklen's approach. From the expert judgment results, Graded English Tasks (GET) received scores ranging from 4.17 to 5.00 which means that the GET developed is good and ready to be used in differentiated instruction in the classroom. The use of GET is proven to accommodate differences in students' readiness to learn, increase students' engagement in learning, and improve students' speaking and presentation skills. GET can be used in differentiated instruction in junior high school English classes.